Paediatric pulmonary disease—are we diagnosing it right? - Rajendran, Priya; Thomas, Silla Varghese; Balaji, Sarath; Selladurai, Elilarasi; Jayachandran, Ganesh; Malayappan, Aravind; Bhaskar, Adhin; Palanisamy, Sivaraman; Ramamoorthy, Thirumalani; Hasini, Sindhu; Hissar, Syed (Frontiers in Pediatrics, 2024)
Background: It has been reported that differential diagnosis of bacterial or viral pneumonia and tuberculosis in infants and young children is complex. This could be due to the difficulty in microbiological confirmation in this age group. In this study, we aimed to assess the utility of a real time multiplex PCR for diagnosis of respiratory pathogens in children with pulmonary TB.: A total of 185 respiratory samples (bronchoalveolar lavage (15), gastric aspirates (98), induced sputum (21), and sputum (51)) from children aged 3-12 years, attending tertiary care hospitals, Chennai, India were included in the study. The samples were processed by NaLC NAOH treatment and subjected to microbiological investigations for Mycobacterium tuberculosis (MTB) diagnosis that involved smear microscopy, Xpert® MTB/RIF testing and liquid culture. In addition, DNA extraction from the processed sputum was carried out and was subjected to a multiplex real time PCR comprising a panel of Bacterial and fungal pathogens.Results: Out of 185 samples tested, a total of 20 samples were positive for MTB by either one or more identification method (Smear, Culture and Genxpert). Out of these 20 MTB positive samples, 15 were positive for one or more bacterial or fungal pathogen with different cycle threshold (CT) value. Among MTB negative patients (n=165), 145 (87%) were positive for one or more than one bacterial or fungal pathogens.The results suggest that tuberculosis could co-exist with other respiratory pathogens causing pneumonia. However, a large-scale prospective study from different geographical setting that uses such simultaneous detection methods for diagnosis of childhood tuberculosis and pneumonia will help in assessing the utility of these tests in rapid diagnosis of respiratory infections.